NUMERICAL ANALYSIS OF OUT-PLANE FAILURE BEHAVIOUR DUE TO CYCLIC LOAD ON CONFINED MASONRY WALL PORTAL STRUCTURE WITH FINITE ELEMENT METHOD - Avhycanti Laventina, Reinata
Indonesia is an island nation prone to natural disasters. This is due to Indonesia being a country that is in the path of the Pacific Ring of Fire which is an active mountain path on earth. This ring of fire stretches from the west coast of South America, continues to the west coast of North America, then circles to Canada, the Kamsatchka peninsula, Japan, through Indonesia, New Zealand and the islands of the South Pacific. The damage that occurred in an earthquake caused many losses and the most damage that occurred in Indonesia was the failure of buildings. Most building failures occur in residential wall failure. Failures that occur on the wall are divided into two types of failures namely out-plane failure and in-plane failure. Examine the behavior of reinforced concrete confined brick wall structure against the out-plane failure of the brick masonry structure. The analysis was carried out on two models of specimens namely brick wall without reinforcement and with two-way reinforcement with diameter of 8 mm with distance of 300 mm. The maximum lateral resistance results for pushover analysis are worth 1381,608 N with a maximum displacement of 3.6 mm before experiencing temporary collapse for a brick wall with a reinforcement of a maximum resistance value of 2169 N with a maximum displacement of 30 mm. In the cyclic analysis, the value of the maximum lateral resistance of the reinforcement wall is 1331,561 N in the thrust phase and 1332.72 N in the tensile phase. The maximum resistance value for walls with reinforcement is 2168.2 N in the thrust phase and 2153.3 N in the tensile phase.